UNDERSTANDING AND UTILIZING E-LEARNING IN LECTURERS OF MKWU UNIVERSITY OF RIAU - Supentri (JURNAL RANDAI, 2020)
E-learning is a learning media that can help teachers or lecturers make it easier to communicate so learning can happen anytime and anywhere as long as it is connected to the internet. Lecturers in general compulsory courses almost every year will enter the semester to conduct training in the use of e-learning in the hope that all lecturers in mkwu can use the facilities provided and can also facilitate lecturers in the administration of assignments, grades and others. However, in the implementation of the training there are still some who consider e-learning not so important, so this research is to look at the understanding and use of e-learning in lecturers at Riau University in Riau. Data were collected using a questionnaire distributed to lecturers participating in the training and then analyzed using descriptive analysis and presented. Based on the results of research conducted it can be concluded that the understanding and use of e-learning in lecturers who understand and use 68% other than that 18% do not understand and also do not use e-learning, other than that 13% are still doubtful. Some things that make not using e-learning are inadequate facilities and infrastructure and besides the desire to take training seriously is also lacking